Effects of Statins on Bone Mineral Density and Fracture Risk: A PRISMA-compliant Systematic Review and Meta-Analysis. Issue 22 (May 2016) - Wang, Zongze; Li, Ying; Zhou, Fengxin; Piao, Zhe; Hao, Jian
Abstract : Abstract: Although observational studies have identified the protective effect of statins on bone health, the effects remain controversial in randomized controlled trials (RCTs). We conducted a meta-analysis of RCTs to evaluate the effects of statins on bone mineral density (BMD) and fracture risk among adults. We searched electronic databases of Medline, Embase, and the Cochrane Central Register of Controlled Trials (CENTRAL) and conducted a bibliography review to identify articles published until May, 2015. Studies included in this meta-analysis should be randomized controlled trials conducted in adults, using statins in the intervention group. Information on changes in BMD or odds ratio, relative risk or hazard ratio (HR) for fracture risk with the corresponding 95% confidence interval (CI) was provided. Two investigators independently reviewed the title or abstract, further reviewed the full-texts and extracted information on study characteristics and study outcomes. Net change estimates of BMD and pooled HR of fracture risk comparing the intervention group with the control group were estimated across trials using random-effects models. Of the relevant 334 citations, 7 trials (including 27, 900 randomized participants in total) meeting the eligibility criteria were included. Of the 7 trials, 5 were conducted to assess the association of statins use with BMD change and 2 with fracture risk. Compared with the control group, statins use was associated with significant increase in BMD of 0.03 g/cm 2 (95% CI: 0.006, 0.053; I 2  = 99.2%; P  < 0.001), but null association with fracture risk, with the pooled HR of 1.00 (95% CI: 0.87, 1.15; I 2  = 0; P  = 0.396). Sensitivity analyses revealed that the associations were consistent and robust. The effect of statins use on bone health among subpopulation could not be identified due to limited number of trials. These findings provide evidence that statins could be used to increase BMD other than decreasing fracture risk in participant with dyslipidemia. In addition, further trials with the primary outcome of bone health-related measurements in subpopulation are warranted to ensure the effect of statins use. Abstract : Supplemental Digital Content is available in the text